2017
DOI: 10.1371/journal.pone.0172063
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the intestinal permeability of rosemary (Rosmarinus officinalis L.) extract polyphenols and terpenoids in Caco-2 cell monolayers

Abstract: Rosemary (Rosmarinus officinalis) is grown throughout the world and is widely used as a medicinal herb and to season and preserve food. Rosemary polyphenols and terpenoids have attracted great interest due to their potential health benefits. However, complete information regarding their absorption and bioavailability in Caco-2 cell model is scarce. The permeation properties of the bioactive compounds (flavonoids, diterpenes, triterpenes and phenylpropanoids) of a rosemary extract (RE), obtained by supercritica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 50 publications
(59 reference statements)
4
47
1
Order By: Relevance
“…Most studies intended to apply BCS for botanical drugs and plant extracts have focused on the intrinsic characteristics of representative compounds of the mixture . As far as we know, this is the first time that both, solubility and permeability, are experimentally established for rutin from an herbal matrix and its BCS category is compared with that for pure compound.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies intended to apply BCS for botanical drugs and plant extracts have focused on the intrinsic characteristics of representative compounds of the mixture . As far as we know, this is the first time that both, solubility and permeability, are experimentally established for rutin from an herbal matrix and its BCS category is compared with that for pure compound.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that using this method to mimic the intestinal absorption is quite efficient since Caco‐2 cells express the typical morphological and functional properties as well as the enzymatic activities of small bowel enterocytes (Lea, ). According to literature, Caco‐2 cell line model has been extensively used to study the bioavailability of a large number of nutrients and bioactive compounds with antioxidant properties, such as polyphenols and terpenoids (Pérez‐Sánchez et al ., ; Achour et al ., ) or carotenoids (Liu et al ., ). Furthermore, a high correlation between the Caco‐2 permeability data and the human enterocytes absorption coefficients in vivo was demonstrated (Chopra et al ., ; Lea, ).…”
Section: Resultsmentioning
confidence: 99%
“…The assessment of polyphenols bioavailability can be conducted in vivo and/or in vitro . Although in vivo assays could offer more advantages in terms of accuracy, a wide number of researchers have used cell cultures, namely Caco‐2 cells, as a useful tool to study the intestinal absorption of phenolic acids and flavonoids (Konishi et al ., ; Pérez‐Sánchez et al ., ; Achour et al ., ). In fact, this colonic line has the ability of differentiating, under normal culture conditions, into a cellular monolayer resembling an intestinal epithelium mimicking a functional intestinal barrier (Lea, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, FCR improvement in the shrimps treated with CEO and CEO‐loaded NPs supplemented diets suggested that the increasing digestibility and in turn the energetic benefits could increase the growth performance, possibly due to its appetite characteristics. It also demonstrated an improvement in the digestive activity and the absorptive capacity of the intestine related to the anti‐inflammatory and antiproliferative effects of the medicinal plants (Pérez‐Sánchez, Borrás‐Linares, Barrajón‐Catalán, Arráez‐Román, González‐Álvarez, Ibáñez,Segura‐Carretero, Bermejo, Micol, ).…”
Section: Discussionmentioning
confidence: 98%